Suspension Stability Ethanol Extract Of Frankincense Gum (Styrax Benzoin) - Nora Susanti; Yosia Gopas Oetama Manik; Jamalum Purba (Universitas Negeri Medan, 2022)
Sap is a very important commodity in the industrial pharmacy, perfumes and medicines contain abundant active compounds of frankincense making resin widely used. Extraction and solvation processes play an important role in the production of stable frankincense extract. One of the widely used preparations is suspension, which is an active compound that does not dissolve in water to become soluble. The purpose of this study was to determine the manufacture of a suspension of frankincense gum extract as an active pharmaceutical ingredient. The method used was precipitation using cosolvent, surfactant and agitation process at 1500 rpm at a temperature of 40oC. Various comparisons were analyzed for phytochemical screening, viscosity and pH. in the most stable formula to be tested, the size of the suspension particles found that frankincense extract was soluble in distilled water with an average particle size is 4.80205 μm. .